Pengembangan E-modul Interaktif Berbasis Android dan Nature of Science Pada Materi Ikatan Kimia dan Gaya Antar Molekul Untuk Menumbuhkan Literasi Sains Siswa - Accraf, Lalu Bhabiet Rinjani; Suryati, Suryati; Khery, Yusran (Hydrogen: Jurnal Kependidikan Kimia, 2019)
Chemical bond sand intermolecular forces have abstract characteristics. The presence of technology in learning media can help students understand the concept. The learning media in question can be in the form of an androidbased interactive e-module that provides convenient accessibility for users. To present the atmosphere of science learning, the e-module can be structured with the orientation of the Nature Of Science. This research and development aims to produce an android-based interactive e-module prototype with the nature of science oriented on chemical bonding and intermolecular forces subject material to foster students’ scientific literacy. This type of research and development study was carried out with the Nieven development model which consisted of 4 stages: (1) preliminary research stage, (2) prototyping stage ,(3) summative evaluation stage, and (4) systematic reflection and documentation stage. However, due to limited resources, this study was carried out until summative evaluation. With the presentation formula and with the categories, the results of expert validation obtained an average presentation of 90% with very feasible categories, and practical test results on chemistry teachers obtained avalue of 95% with very feasible categories and the results of limited group trials obtained 85% with very decent category. Therefore, it can be concluded that the interactive e-module prototype that developed is very feasible and can be proceed to abroader stage in fostering students’ literacy skills.